PEMASARAN BENIH GURAMI DI DESA JAMBIDAN KABUPATEN BANTUL - , MELITHA RUKMANA SARI, Ir. Suparjo Supardi Djasmani, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine marketing structure of gouramy seed, identify functions, channels and farmer's share of marketing gouramy seed, and to know the margin of marketing gouramy seed in the Jambidan Village, Bantul. The respondents consist of 11 seeds breeders of gouramy and a intermediate trader. Market structure, channels and functions of marketing determined by observing all the marketing activities of gouramy seeds from producer to the final consumer. The value of marketing margins and the farmer's share is calculated by using the formula of marketing margins and farmer's share (Hanafiah and Saefuddin, 1986). The results showed that the marketing channels of gouramy seed consists of two channels, namely channel I (seed breeders of gouramy in Jambidan - consumers) and channel II (seed breeder of gouramy in Jambidan â intermediate trader - consumers). Marketing functions performed by seed breeders of gouramy and intermediate trader are purchasing, sales, packaging and market information functions. Intermediate traders also performed the functions of transporting, storing and grading. Market structure from seeds breeders of gouramy was perfectly competitive market. Market structure from traders was monopoly markets. The largest mean of the marketing margin on the channel I was founded in 5,3 cm or rokok mild size (Rp.554,19/ seed) and the smallest was2,3 cm or jempol size (Rp. 4,97/seed). In the channel II, the largest mean of marketing margin was 5,3 cm or rokok mild size (Rp. 899,38/ seed) and the smallest was tiga empat size (Rp.105,33/ seed). Farmer's share in channel I was greater than the channel II. Based on the analysis, it can be concluded that the marketing channel I has a smaller total margin, the highest value of the farmer's share, and the highest benefit against the cost.